Learning about bird education in Malaysia through 3D simulation - Rosli, Mohamad Ashraf Hafizi; Dahlan, Azlin; Mohd Yasin, Anita (College of Computing, Informatics, and Mathematics, 2025)
Bird species are classified as endangered when they are at risk of extinction and unlikely to survive due to various factors that negatively impact their populations. Birds play crucial roles in ecosystems, and their extinction can disrupt the food chain, leading to significant ecological imbalances. This study aims to assess public awareness regarding endangered bird species and their threatened habitats. The findings will provide insights into the impact of this awareness on the conservation of these birds and their environments among the public. A questionnaire was conducted to assess participants' knowledge and awareness on this matter. The questionnaire consists of two parts: a pre-questionnaire administered before the participants play the game, and a post-questionnaire administered after they have played the game. This project employs the Waterfall technique, a development process that is systematic and linear. The model that has been employed on this project is the GameBased Learning concept. The result showed that the effectiveness of this game was successful after calculated result of evaluation which is 93.34% of improvement and 67.2% of table overview using SGES module. The limitations of this project include a lack of cross platform compatibility, absence of multiplayer functionality, and support for English speakers only. To address these limitations, future development will be conducted